Kurikulum Cinta sebagai Fondasi Manajemen Pendidikan Islam: Integrasi Nilai Spiritual, Humanistik, dan Pedagogis - Aisyah, Siti (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Islamic Education Management (MPI) has long been oriented toward technical-administrative aspects and cognitive achievement, while affective dimensions such as love, empathy, and compassion have not been systematically managed within the curriculum. This condition implies that educational practices often lose their humanistic and spiritual essence, despite Islamic education normatively carrying values of mercy and morality. Previous studies mostly discussed Islamic education curriculum from normative, competency, or policy perspectives, but rarely placed “love” as a managerial foundation in curriculum management. The research gap lies in the absence of love values as a conceptual framework that holistically connects spiritual, humanistic, and pedagogical dimensions. This study offers novelty by conceptualizing a “curriculum of love” as a paradigm of education management that is not only ethical-normative but also operational in planning, implementation, and evaluation of Islamic education curriculum. The research questions are: first, how can the concept of a curriculum of love be positioned as a foundation in Islamic Education Management; and second, how can the integration of spiritual, humanistic, and pedagogical values be realized in curriculum management. This study employs library research with conceptual and philosophical approaches, analyzing classical and contemporary literature relevant to MPI, humanistic education, and Islamic values. The findings show that the curriculum of love functions as an integrative framework that strengthens value orientation in education management, encourages student-centered learning practices, and reaffirms the purpose of Islamic education as a process of forming faithful, moral, and holistic personalities.